2010
DOI: 10.1097/mpg.0b013e3181cb42ee
|View full text |Cite
|
Sign up to set email alerts
|

Serum Markers May Distinguish Biliary Atresia From Other Forms of Neonatal Cholestasis

Abstract: Background Biliary atresia (BA) is the most serious liver disease in infants. Diagnosis currently depends on surgical exploration of the biliary tree. Non-invasive tests that distinguish BA from other types of neonatal liver disease are not available. Methods To identify potential serum biomarkers that classify children with neonatal cholestasis, we performed 2-dimensional difference gel electrophoresis, statistical analysis, and tandem mass spectrometry using serum samples from 19 infants with BA and 19 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Other candidate biomarkers previously reported include miR-140-3p (31), miR-200b/429 (14), miR-4429, and miR-4689 (32), but with lower sensitivity (66–83%) and specificity (79–83%) and no prospective validation. In a separate study, the use of 2-dimensional gel electrophoresis with tandem mass spectrometry found a combination of 11 proteins as biomarkers; the small cohort size and relatively large number of protein analytes selected in this study limit the interpretation of the results and its potential use in clinical practice (33). Altogether, these data suggest a superior value for MMP-7 + GGT among circulating biomarkers of BA.…”
Section: Discussionmentioning
confidence: 99%
“…Other candidate biomarkers previously reported include miR-140-3p (31), miR-200b/429 (14), miR-4429, and miR-4689 (32), but with lower sensitivity (66–83%) and specificity (79–83%) and no prospective validation. In a separate study, the use of 2-dimensional gel electrophoresis with tandem mass spectrometry found a combination of 11 proteins as biomarkers; the small cohort size and relatively large number of protein analytes selected in this study limit the interpretation of the results and its potential use in clinical practice (33). Altogether, these data suggest a superior value for MMP-7 + GGT among circulating biomarkers of BA.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies have found that serum GGTP levels are frequently elevated in other forms of neonatal cholestasis (16, 17). Wang et al used a proteomic approach to identify 11 serum proteins significantly altered in BA compared to non-BA cholestasis (18). A classifier derived from the proteins correctly identified nine of ten BA and non-BA cholestatic control samples.…”
Section: Discussionmentioning
confidence: 99%
“…The Apolipoprotein E has been found to be useful in the diagnostic workup as the serum levels have been consistently elevated in biliary atresia[33]. Rafeey et al[34] in a recent study showed Apolipoprotein E to have positive predictive value of 71% and negative predictive value of 67% in differentiating biliary atresia from other neonatal cholestatic disorders, indicating that its utility as a stand-alone diagnostic test is limited.…”
Section: Investigationsmentioning
confidence: 99%